Relationship between muscle forces, joint loading and utilization of elastic strain energy in equine locomotion - Harrison, S. M.; Whitton, R. C.; Kawcak, C. E.; Stover, S. M.; Pandy, M. G. (The Journal of Experimental Biology, 2010)
Storage and utilization of strain energy in the elastic tissues of the distal forelimb of the horse is thought to contribute to the excellent locomotory efficiency of the animal. However, the structures that facilitate elastic energy storage may also be exposed to dangerously high forces, especially at the fastest galloping speeds. In the present study, experimental gait data were combined with a musculoskeletal model of the distal forelimb of the horse to determine muscle and joint contact loading and muscle-tendon work during the stance phase of walking, trotting and galloping. The flexor tendons spanning the metacarpophalangeal (MCP) joint - specifically, the superficial digital flexor (SDF), interosseus muscle (IM) and deep digital flexor (DDF) - experienced the highest forces. Peak forces normalized to body mass for the SDF were 7.3±2.1, 14.0±2.5 and 16.7±1.1 N kg-1 in walking, trotting and galloping, respectively. The contact forces transmitted by the MCP joint were higher than those acting at any other joint in the distal forelimb, reaching 20.6±2.8, 40.6±5.6 and 45.9±0.9 N kg-1 in walking, trotting and galloping, respectively. The tendons of the distal forelimb (primarily SDF and IM) contributed between 69 and 90% of the total work done by the muscles and tendons, depending on the type of gait. The tendons and joints that facilitate storage of elastic strain energy in the distal forelimb also experienced the highest loads, which may explain the high frequency of injuries observed at these sites.